Analyzing Marketing Communication Strategies for "Satu Nagari Satu Event" Program in West Sumatra - Mandalia, Siska; Gautama, Mohammad Isa; Hidayat, Taufik (Mediator: Jurnal Komunikasi, 2024)
This study analyzed the marketing communication strategies employed for the "Satu Nagari Satu Event" program in Tanah Datar Regency, West Sumatra. The program, aimed at promoting cultural engagement and community participation, underscores the significance of effective marketing communication in achieving its objectives. The analysis begins by outlining the core goals and context of the "Satu Nagari Satu Event" program, establishing a foundation for the subsequent evaluation. By examining the clarity and consistency of the program's messaging, the analysis sheds light on its ability to convey its value proposition. Channels of communication, both traditional and digital, are scrutinized to assess their reach and impact. In recognition of the cultural context, the analysis probes the extent to which marketing communication resonates with the local customs and traditions of Tanah Datar Regency. The evaluation concludes by examining key performance indicators such as event attendance, website traffic, and social media engagement, providing insights into the success of the marketing communication strategies. By merging these insights, the analysis offers recommendations for refining the program's marketing communication approaches and enhancing its impact on cultural engagement and community involvement.